2014
DOI: 10.1063/1.4891259
|View full text |Cite
|
Sign up to set email alerts
|

Charge compensation of head-to-head and tail-to-tail domain walls in barium titanate and its influence on conductivity

Abstract: The effect of the polarization charge compensation by ionic and electronic space charges on domain properties in ferroelectrics with semiconducting features is considered, in particular, the conductivity of head-to-head and tail-to-tail domain walls is studied. It is shown that the domain wall conductivity that is enhanced by electrons or holes depends on the configuration and the types of domains as well as on the energy levels and concentrations of the defects involved. Phase field simulation results are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…They are sufficient to estimate the structural width to be ~1 nm, but insufficient to judge about the charge compensation and transport mechanisms. The latter are the subject of modelling 23 25 . It is expected thus that the conductive width w of charged domain walls is about 10 nm, exceeding the width of neutral walls by roughly one order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are sufficient to estimate the structural width to be ~1 nm, but insufficient to judge about the charge compensation and transport mechanisms. The latter are the subject of modelling 23 25 . It is expected thus that the conductive width w of charged domain walls is about 10 nm, exceeding the width of neutral walls by roughly one order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The dark conductivity of LN crystals is very low 29 ; at room temperature it is well below 10 −15 (Ω cm) −1 . This corresponds to a very slow (with relaxation times of months or years) migration of numerous ions 35 , so that the electronic compensation of CDWs via the band bending 13 , 23 25 looks the most natural on a realistic time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Due to impurities or the aging effect, charges can accumulate at the interface of the layered composite. [51,52] Here, we introduce thin charge interphase layers between FE/RE interfaces in the finite element simulation to investigate the effect of electrical decoupling of layers, viz. Phase-field simulations have shown that space charges can influence the stability of the domain structure.…”
Section: Influence Of Interface Chargementioning
confidence: 99%
“…Nevertheless, also nanodomain patterns have been observed by experiments [11]. Domain walls are investigated by experiments and simulations whereas especially 180°domain walls have been examined [12][13][14][15][16]. However, experiments at very low temperatures are difficult to realise and there are no detailed domain wall studies available for rhombohedral barium titante.…”
Section: Introductionmentioning
confidence: 99%